ADAPTING (TO) THE ENVIRONMENT: NAVIGATING HOUSING AND TRANSPORTATION. (11th November 2018) - Ward, C R; Miller, J; Raue, M; Brady, S; D'Ambrosio, L A; Ellis, D; Felts, A; Coughlin, J F
Abstract: This presentation will explore the transportation and housing adaptations the MIT AgeLab Lifestyle Leaders have made to continue aging successfully. The first portion will focus on transportation and mobility, which are essential to access healthcare and provide opportunities for social interaction. We will present an overview of transportation issues faced by the 85+, including giving up the keys and adapting to new modes of transportation, and how changes in mobility have affected their abilities to stay healthy, safe and engaged. Participants expressed friction, frustration and fatigue related to the lack of choice and control over transportation options. The second portion of the presentation will discuss choice of residence, moving and downsizing in later life. Approximately half of the Lifestyle leaders have moved within the past ten years to receive care for their spouse, live in a place better suited for their lifestyle, be closer to family, or save money.